Renal biopsy in children with steroid-dependent nephrotic syndrome - Skalova, S; Podhola, M; Geier, P; Tichy, T (Bratislavske lekarske listy, 2009)
BACKGROUND: There is lack of consensus on the necessity of renal biopsy in children with steroid-dependent nephrotic syndrome (SDNS) prior to cytotoxic therapy. OBJECTIVES: To retrospectively evaluate: (a) the benefit of renal biopsy (RB) prior to cyclophosphamide therapy; (b) relationship between histopathologic results of RB samples and clinical course in children with SDNS. PATIENTS, MATERIALS AND METHODS: RB was performed in 18 SDNS patients (11 boys and 7 girls). The mean age of the children at the time of nephrotic syndrome (NS) diagnosis was 6.4 +/- 3.9 years and 9.7 +/- 4.3 years at the time of RB. Following the RB, all children received prednisone and cyclophosphamide treatment for 12 weeks. Duration of remission and relapse rate was recorded. RESULTS: The histologic evaluation revealed minimal change disease (MCD; n = 14) and IgM nephropathy (n = 4). These results didn't affect the ongoing therapy. MCD patients had longer remission compared to IgM nephropathy (3.2 +/- 1.5 vs 1.7 +/- 0.8 years; p = 0.05). Relapse rate did not differ significantly between MCD and IgM nephropathy (p = 0.22). The duration of remission was inversely correlated to relapse rate after the treatment (r = -0.66, p = 0.01). CONCLUSION: We suggest that RB prior to cyclophosphamide therapy is not necessary in patients with SDNS (Tab. 2, Ref. 14). Full Text (Free, PDF) www.bmj.sk.
Keywords: Immunosuppressive Agents; jehlová biopsie; cyklofosfamid; prednison; Remission Induction; Glucocorticoids; Biopsy, Needle; mužské pohlaví; glukokortikoidy; dítě; Child; ženské pohlaví; Cyclophosphamide; imunosupresiva; nefrotický syndrom; Humans; Nephrotic Syndrome; Prednisone; ledviny; indukce remise; Kidney; Female; lidé; Male